Neyraiella distinctus n. sp. (Oxyurida, Blattophilidae) parasite of nymphs of Gryllodes laplatae sauss (Orthoptera, Gryllidae) in Argentina - Camino, Nora Beatriz (2002)
Neyraiella distinctus n. sp. was found parasitizing nymphs of the cricket Gryllodes laplatae Sauss in City Bell, Argentina. This species was characterized by having the excretory pore in the posterior end of the basal bulb, vulva protruding with one lip well developed in the 1/3 end of the body, anus of the female with wings, male with a single spicule without any sculpture, gubernaculum and bursa are absent, six pairs of genital papillae arranged in two preanal pairs, one adanal pair and three postanal pairs, and the tail appendage in both sexes was short and conic.